Infestation and population dynamics of insects on stored cassava and yams chips in Benin, West Africa - Gnonlonfin, G.J.B.; Hell, K.; Siame, A.B.; Fandohan, P. (2008)
Natural insect infestation in cassava (Manihot esculenta Crantz subspecies esculenta) and yam (Dioscorea spp.) chips was evaluated during two consecutive storage seasons (2003Ð2004 and 2004Ð2005) in two agroecological zones of Benin (Northern Guinea Savanna [NGS] and Sudan Savanna [SS]). The insects infesting chips were collected, identiÞed, and counted, they included Prostephanus truncatus (Horn) (Coleoptera: Bostrychidae), Cathartus quadricollis (Guerin) (Coleoptera: Silvanidae), Carpophilus dimidiatus (F.) (Coleoptera: Nitidulidae), Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), and Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae). P. truncatus and C. quadricollis were observed with a higher prevalence on cassava than on yam chips. During both seasons after 3 mo of storage, all (100%) cassava chip samples were infested with P. truncatus and C. quadricollis in both agroecological zones, whereas yam chips only showed lower infestation rates of 59.5 and 19.1% for P. truncatus and C. quadricollis, respectively, at the end of storage in 2003Ð2004. During the 2004Ð2005 season after 3 mo of storage infestation rate in yam chips was 66 and 24% in NGS and 100 and 0% in SS for P. truncatus and C. quadricollis, respectively, showing that insect infestation levels vary signiÞcantly with commodity, year, and ßuctuate during the storage season.